Correlation and Reliability Analyses among the Upper Cervical Rotation-Flexion Test, Upper Cervical Flexion-Extension Test, and Upper Cervical Flexion Angle Measurement Using Radiography - Do, KwangSun (Int J Environ Res Public Health, 2020)
(1) Background: The cervical rotation-flexion test is one method of measuring the range of motion of the upper cervical spine; however, this test has not been investigated in detail. The aim of this study was to investigate the reliability and concurrent validity of the upper cervical rotation-flexion test. (2) Methods: Twenty-five healthy individuals (13 women and 12 men) participated in this study. The participants underwent radiography, the upper cervical flexion-extension test, and the upper cervical rotation-flexion test in a sitting position while wearing a cervical goniometer to measure the upper cervical flexion angle. Three experienced physical therapists administered the upper cervical rotation-flexion test using the cervical device, twice for each participant. Inter-rater and intra-rater reliabilities were evaluated using the intraclass correlation coefficient (95% confidence interval). (3) Results: The inter-rater and intra-rater reliability values of the total scores were excellent. The results of the upper cervical rotation-flexion test significantly correlated with those of the radiographic evaluation of the upper cervical flexion angle (r = 0.80, p < 0.001) and those of the upper cervical flexion-extension test (r = 0.77, p < 0.001). Significant correlations among the three test results were observed. (4) Conclusions: The findings of this study suggest that the upper cervical rotation-flexion test is meaningful for independently measuring the upper cervical flexion angle.